An electrochemiluminescence method for detecting iron ions

Through the modified electrode by Phen/PTCA/NH2-MIL-125/GCE, the electrostatic binding of PTCA and NH2-MIL-125 and the selective binding of Phen, the complexity and low sensitivity of detecting iron ions in lithium hexafluorophosphate in the prior art were solved, and high sensitivity and selective iron ion detection was achieved.

CN116183702BActive Publication Date: 2025-04-25JIANGSU TAIJI MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211592754.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-09
Filing Date
2022-12-13
Publication Date
2025-04-25
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The existing methods for detecting iron ions in lithium hexafluorophosphate are complex in operation, time-consuming, costly and low in sensitivity, making it difficult to effectively detect iron ions with lower content in lithium batteries.

Method used

The Phen/PTCA/NH2-MIL-125/GCE modified electrode was used as an electrochemiluminescence sensor. The electrostatic binding of PTCA and NH2-MIL-125 and the selective binding of Phen to achieve high sensitivity detection of iron ions.

Benefits of technology

The detection sensitivity and selectivity of iron ions are improved, and the selective rapid detection of iron ions in lithium hexafluorophosphate is achieved, with the minimum detection limit reaching 3.5×10-15mol/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116183702B_ABST
    Figure CN116183702B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of metal ion detection, and specifically to an electrochemiluminescence method for detecting iron ions, and in particular to an electrochemiluminescence method for detecting iron ions in lithium hexafluorophosphate. The method uses a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as a working electrode for electrochemiluminescence testing, a platinum electrode as an auxiliary electrode, and Ag / AgCl as a reference electrode to form a three-electrode system, and uses an electrochemiluminescence method to detect iron ions. The detection range of the iron ion concentration of the method is 1.0×10 ‑14 mol / L~1.0×10 ‑7 mol / L, the minimum detection limit is 3.5×10 ‑15 mol / L. The method of the present invention is used to detect iron ions in lithium hexafluorophosphate and has the advantages of high sensitivity, strong specificity and simple operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal ion detection, in particular to an electrochemiluminescence method for detecting iron ions, and in particular to an electrochemiluminescence method for detecting iron ions in lithium hexafluorophosphate. Background Art

[0002] With the continuous advancement of the national new energy vehicle development strategy, the demand for lithium-ion batteries and lithium salts will continue to grow. As an irreplaceable important and key material for the new energy industry, lithium hexafluorophosphate has strong advantages in comprehensive performance indicators and industrialization costs, and will continue to be an important lithium salt electrolyte for some time to come. At present, the mainstream process technology methods for commercial production are gas-solid method, organic solvent method, ion exchange method and hydrogen fluoride solvent method. Regardless of the method, iron ions are easily introduced into the synthesis process. Due to the presence of iron ions, the charge and discharge performance of lithium-ion batteries will be affected.

[0003] Currently, the methods reported for detecting iron ions in lithium hexafluorophosphate include spectrophotometry, plasma emission spectroscopy, and atomic absorption spectrometry. However, these methods are complex, time-consuming, and costly, and the sensitivity of detection is not high. Electrochemiluminescence (ECL) is a chemiluminescence caused by electrochemical reactions. It has attracted widespread attention due to its high sensitivity, strong reaction controllability, and simple instrumentation. It is a new analytical method with great development potential. Summary of the invention

[0004] In order to further improve the detection sensitivity and selectivity of iron ions in lithium hexafluorophosphate, the present invention is to provide an electrochemiluminescence method for detecting iron ions, by fixing a Ti-based MOFs material (NH2-MIL-125) with perylene tetracarboxylic acid (PTCA), and then preparing a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as a working electrode, and quantitatively detecting an electrochemiluminescence analysis method for iron ions in lithium hexafluorophosphate. Since PTCA and NH2-MIL-125 are closely combined by electrostatic action, the luminescence intensity of the PTCA / NH2-MIL-125 / GCE modified electrode is not only high and stable, but also can be selectively combined with iron ions based on o-phenanthroline (Phen), so as to achieve a linear relationship between the electroluminescence intensity of the Phen / PTCA / NH2-MIL-125 / GCE modified electrode and the concentration of iron ions. The present invention not only has the advantages of high sensitivity, strong specificity, wide linear range and simple instrumentation of electrochemiluminescence analysis, but also realizes selective rapid detection of iron ions in lithium hexafluorophosphate.

[0005] The present invention is achieved through the following technical solutions:

[0006] The invention provides an electrochemiluminescence method for detecting iron ions. A Phen / PTCA / NH2-MIL-125 / GCE modified electrode is used as a working electrode for electrochemiluminescence test, a platinum electrode is used as an auxiliary electrode, and Ag / AgCl is used as a reference electrode to form a three-electrode system, and the electrochemiluminescence method is used to detect iron ions.

[0007] Although the electrochemiluminescence method itself has good sensitivity, it is difficult to detect low-content iron ions in lithium hexafluorophosphate of lithium batteries. In order to improve the detection sensitivity and selectivity of iron ions, the present invention first uses perylenetetracarboxylic acid (PTCA) to fix amino Ti-based MOFs (NH2-MIL-125), so that PTCA and NH2-MIL-125 are tightly combined through electrostatic interaction, thereby improving the luminescence intensity and luminescence stability of the PTCA / NH2-MIL-125 / GCE modified electrode.

[0008] In order to further improve the selectivity for iron ions, the present invention further modifies the electrode using o-phenanthroline (Phen) to obtain a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as a working electrode for an electrochemiluminescence method, thereby improving the selectivity for iron ions and achieving selective rapid detection of iron ions in lithium hexafluorophosphate.

[0009] Preferably, the preparation of the Phen / PTCA / NH2-MIL-125 / GCE modified electrode comprises the following steps:

[0010] (1) adding NH2-MIL-125 material and perylene tetracarboxylic acid into an ethanol solution, dispersing them uniformly, centrifuging and washing and drying to obtain a light red powder, namely the PTCA / NH2-MIL-125 composite material;

[0011] (2) dispersing the PTCA / NH2-MIL-125 composite material obtained in step (1) in DMF to obtain a DMF solution of the PTCA / NH2-MIL-125 composite material;

[0012] (3) The DMF solution of the PTCA / NH2-MIL-125 composite material obtained in step (2) and the o-phenanthroline aqueous solution are mixed, and then drop-coated on the glassy carbon electrode, and then dried under an infrared lamp to obtain a Phen / PTCA / NH2-MIL-125 / GCE modified electrode.

[0013] Furthermore, the preparation method of the NH2-MIL-125 material is:

[0014] Perylenetetracarboxylic acid and 2-aminoterephthalic acid are added to a mixed solution of DMF and methanol, mixed evenly to obtain a yellow milky liquid, which is then transferred to a high-pressure reactor for reaction. After the reaction is completed, the product is centrifuged, washed, and dried to obtain a yellow powder, namely the NH2-MIL-125 material.

[0015] Furthermore, the preparation method of perylene tetracarboxylic acid is: dissolving perylene tetracarboxylic dianhydride in NaOH, then stirring the reaction to obtain a yellow-green solution, dripping HCl until complete precipitation, and washing with deionized water and drying to obtain a dark red powder, namely perylene tetracarboxylic acid.

[0016] Optionally, the mass ratio of the NH2-MIL-125 material and perylene tetracarboxylic acid in step (1) is 3:1, and the total concentration of the solution obtained after the two substances are added with ethanol is 1 mg / mL;

[0017] The mass concentration of the PTCA / NH2-MIL-125 composite material in the DMF solution of the PTCA / NH2-MIL-125 composite material in step (2) is 1 mg / mL;

[0018] The concentration of the o-phenanthroline aqueous solution in step (3) is 5.0×10 -3 mol / L.

[0019] In order to more clearly illustrate the technical solution of the present invention, the electrochemical luminescence method for detecting iron ions provided by the present invention comprises the following specific steps:

[0020] (1) preparing a PBS buffer solution containing K2S2O8;

[0021] (2) Drawing of standard curve:

[0022] Adding iron ions to the PBS buffer solution containing K2S2O8 obtained in step (1) to obtain a series of iron ion standard solutions with different concentrations;

[0023] A three-electrode system is formed by using a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as a working electrode, a platinum electrode as an auxiliary electrode, and Ag / AgCl as a reference electrode. The three-electrode system is immersed in the above-mentioned iron ion standard solutions of different concentrations, and the PBS buffer solution containing K2S2O8 obtained in step (1) is used as a blank solution. Cyclic voltammetry is performed in the electrochemical window range of -1.6 to 0 V with a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s. The potential-luminescence intensity curve is recorded, and a linear relationship between the difference in luminescence intensity before and after the addition of iron ions and the logarithm of the iron ion concentration is established to obtain a corresponding linear regression equation, and the corresponding curve is the standard curve;

[0024] (3) Sample testing

[0025] The iron ion-containing sample to be tested is pretreated, and then the luminescence intensity is tested according to the method and test conditions described in step (2), and the iron ion concentration in the sample to be tested is calculated using the linear regression equation obtained in step (2).

[0026] Preferably, the molar concentration of K2S2O8 in the PBS buffer solution containing K2S2O8 in step (1) is 0.05 mol / L, the molar concentration of PBS is 0.1 mol / L, and the pH of the PBS buffer solution containing K2S2O8 is 7.5.

[0027] Preferably, the concentration range of the iron ion standard solution in step (2) is 1.0×10 -14 mol / L~1.0×10 -7 mol / L, within this concentration range, the electrochemical luminescence intensity is linearly related to the iron ion. The soaking time is 15 min.

[0028] More preferably, the electrochemical method of the present invention is used to detect iron ions in lithium hexafluorophosphate.

[0029] Now for the prior art, the beneficial effects of the present invention are:

[0030] (1) The present invention uses PTCA to fix the aminated Ti-based MOFs material (NH2-MIL-125), and the obtained PTCA / NH2-MIL-125 composite material has high luminescence intensity and stability. Since the aminated NH2-MIL-125 has a strong adsorption capacity for o-phenanthroline (Phen), it is easy to prepare Phen and PTCA / NH2-MIL-125 composite materials to jointly modify glassy carbon electrodes (Phen / PTCA / NH2-MIL-125 / GCE), which are used as electrochemical luminescence sensors. Since Phen has the ability to selectively bind to iron ions in the solution, when iron ions bind to Phen of the modified electrode, the iron ions are selectively enriched on the modified electrode, thereby inducing quenching of the electroluminescence of the PTCA / NH2-MIL-125 composite material, and the quenching light intensity increases with the increase of iron ion concentration.

[0031] (2) Based on the above principle, an electrochemiluminescent sensor for iron ions (Phen / PTCA / NH2-MIL-125 / GCE) was successfully prepared. The luminescence intensity of the sensor has a good linear relationship with the iron ion concentration. Compared with other sensors in the prior art, it has the advantages of high sensitivity and strong specificity. The minimum detection limit of iron ions that can be detected by the electrochemiluminescence method of the present invention is 3.5×10 -15 mol / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a standard curve of the difference in luminescence intensity of the modified electrode Phen / PTCA / NH2-MIL-125 / GCE before and after the addition of iron ions in Example 1 of the present invention and the logarithm of the iron ion concentration. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] Example 1

[0035] This embodiment provides an electrochemiluminescence method for detecting iron ions, using a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as a working electrode for electrochemiluminescence testing, a platinum electrode as an auxiliary electrode, and Ag / AgCl as a reference electrode to form a three-electrode system, and electrochemiluminescence is used to detect iron ions.

[0036] The specific steps include:

[0037] (1) Preparation of PTCA / NH2-MIL-125 composites

[0038] 2.4 mL of isopropyl titanate and 2.2 g of 2-aminoterephthalic acid were added to a mixed solution of 20 mL of DMF and 20 mL of methanol, and the mixture was uniformly mixed by ultrasonication. The obtained yellow emulsion was poured into a 50 mL high-pressure reactor, and heated at 150 ° C in a vacuum drying oven for 48 h. The mixture was washed three times with methanol and DMF respectively and centrifuged, and dried at 60 ° C to obtain a yellow powder, which is the NH2-MIL-125 material.

[0039] Dissolve 0.1 g of perylene tetracarboxylic dianhydride (PTCDA) in 10 mL of 0.1 M NaOH solution and stir at 80 °C for 2 h to obtain a yellow-green solution. Then, add 1.0 M HCl dropwise until complete precipitation. Wash the precipitate with deionized water and dry at 60 °C to obtain a dark red powder, which is PTCA.

[0040] 15 mg of the NH2-MIL-125 material and 5 mg of PTCA prepared above were added to 20 mL of ethanol, and then ultrasonicated for 1 hour, and then stirred at a stirring rate of 1080 rpm in a magnetic stirrer for 24 hours. After stirring, the mixture was centrifuged and washed with ethanol and deionized water respectively. Finally, the washed product was placed in a vacuum drying oven and dried at 60°C to obtain a light red powder, which is the perylenetetracarboxylic acid (PTCA) fixed amino Ti-based MOFs (NH2-MIL-125) composite material (PTCA / NH2-MIL-125).

[0041] 10 mg of the above PTCA / NH2-MIL-125 composite material was dispersed in 10 mL of DMF for use.

[0042] (2) Preparation of o-phenanthroline solution

[0043] Accurately weigh o-phenanthroline and dissolve it in 50 mL of deionized water to a concentration of 5.0 × 10 -3 mol / L for use.

[0044] (3) Preparation of Phen / PTCA / NH2-MIL-125 / GCE modified electrode

[0045] Take 1 mL of the DMF solution of the above PTCA / NH2-MIL-125 composite material and 100 μL of the o-phenanthroline solution and mix them for 1 hour to obtain the o-phenanthroline modified PTCA / NH2-MIL-125 composite Phen / PTCA / NH2-MIL-125, take 2 μL of Phen / PTCA / NH2-MIL-125 and drop it on a clean glassy carbon electrode to obtain a Phen / PTCA / NH2-MIL-125 / GCE modified electrode. The Phen / PTCA / NH2-MIL-125 / GCE modified electrode is placed under an infrared lamp for drying, and can be used as an electrochemiluminescent sensor for selectively detecting iron ions in lithium hexafluorophosphate.

[0046] (4) Drawing of standard curve

[0047] Prepare a 0.1 mol / L PBS buffer solution with a pH of 7.5 and containing 0.05 mol / L K2S2O8.

[0048] A three-electrode system was composed of a Phen / PTCA / NH2-MIL-125 / GCE modified electrode as the working electrode, a platinum electrode as the auxiliary electrode, and Ag / AgCl as the reference electrode. The three-electrode system was immersed in the above-mentioned PBS buffer solution containing a series of different concentrations of iron ions and K2S2O8 for 15 min, and a 0.1 mol / L PBS buffer solution at pH = 7.5 containing 0.05 mol / L K2S2O8 was used as a blank solution to detect the luminescence intensity.

[0049] The three-electrode system was placed in a series of different concentrations (1.0×10 -14 mol / L、1.0×10 -13 mol / L、1.0×10 -12 mol / L、1.0×10 -11 mol / L、1.0×10 -10 mol / L、1.0×10 -9 mol / L、1.0×10 -8 mol / L and 1.0×10 -7 mol / L) of iron ions and a 0.1mol / L PBS buffer solution with a pH value of 7.5 containing 0.05mol / LK2S2O8, with a 0.1mol / L PBS buffer solution with a pH value of 7.5 containing 0.05mol / LK2S2O8 as a blank solution, cyclic voltammetry scanning was performed within the electrochemical window range of -1.6 to 0V, a photomultiplier tube high voltage of 800V, and a scanning speed of 0.1V / s, and the potential-luminescence intensity curve (E-ECL) was recorded. The linear relationship between the luminescence intensity difference before and after the addition of iron ions and the logarithm of the iron ion concentration was established, and the corresponding linear regression equation was obtained as follows: △I ECL =15463.3492+1063.2886LogC(mol / L), the correlation coefficient (R) is 0.9964. The detection range of the linear regression equation is 1.0×10 -14 mol / L~1.0×10 -7 mol / L, the minimum detection limit is 3.5×10 -15 mol / L.

[0050] (5) Testing of samples to be tested

[0051] Accurately weigh 0.5 g of the lithium hexafluorophosphate sample to be tested, add it to 100 mL of 0.1 mol / L PBS buffer solution with a pH of 7.5 and containing 0.05 mol / L K2S2O8, and test it under the same electrochemiluminescence test conditions as step (4), record the luminescence intensity, and then use the linear regression equation corresponding to step (4) to calculate the concentration of iron ions in the lithium hexafluorophosphate sample to be tested. The results are listed in Table 1.

[0052] Comparative Example 1

[0053] (1) Preparation of PTCA / NH2-MIL-125 / GCE modified electrode

[0054] Use a microinjector to pipette 2.0 μL of the DMF solution of 1.0 mg / mL PTCA / NH2-MIL-125 composite material prepared in Example 1 and drop it on the surface of a clean glassy carbon electrode and dry it at room temperature to obtain a PTCA / NH2-MIL-125 / GCE modified electrode, which is used as an electrochemiluminescence sensor for detecting iron ions in lithium hexafluorophosphate.

[0055] (2) Drawing of standard curve

[0056] Prepare a 0.1 mol / L PBS buffer solution with a pH of 7.5 and containing 0.05 mol / L K2S2O8.

[0057] The PTCA / NH2-MIL-125 / GCE modified electrode was used as the working electrode, the platinum electrode as the auxiliary electrode, and the Ag / AgCl as the reference electrode to form a three-electrode system. The luminescence intensity was detected using a 0.1 mol / L PBS buffer solution with pH = 7.5 containing 0.05 mol / L K2S2O8 as the blank solution. The three-electrode system was placed in a series of different concentrations (1.0×10 -14 mol / L、1.0×10 -13 mol / L、1.0×10 -12 mol / L、1.0×10 -11 mol / L、1.0×10 -10 mol / L、1.0×10 -9 mol / L、1.0×10 -8 mol / L and 1.0×10 -7 mol / L) of iron ions and a 0.1 mol / L PBS buffer solution of pH 7.5 containing 0.05 mol / L K2S2O8, in the electrochemical window range of -1.6 to 0 V, with a photomultiplier tube high voltage of 800 V and a scanning speed of 0.1 V / s, cyclic voltammetry scanning was carried out, and the E-ECL curve was recorded. The linear relationship between the difference in luminescence intensity before and after the addition of iron ions and the logarithm of the iron ion concentration was established, and the corresponding linear regression equation was obtained.

[0058] (3) Sample testing

[0059] Accurately weigh 0.5 g of the lithium hexafluorophosphate sample to be tested, add it to 100 mL of 0.1 mol / L PBS buffer solution at pH 7.5 containing 0.05 mol / L K2S2O8, and test it under the same electrochemiluminescence test conditions as step (2), record the luminescence intensity, and then use the linear regression equation corresponding to step (2) to calculate the concentration of iron ions in the sample to be tested. The results are listed in Table 1.

[0060] Comparative Example 2

[0061] (1) Preparation of Phen / GCE modified electrodes

[0062] Use a microinjector to pipette 2.0 μL of the solution prepared in Example 1 to obtain a concentration of 5.0×10 -3 mol / L o-phenanthroline solution was dropped onto the surface of a clean glassy carbon electrode and dried at room temperature to obtain a Phen / GCE modified electrode, which was used as an electrochemiluminescent sensor for detecting iron ions in lithium hexafluorophosphate.

[0063] (2) Drawing of standard curve

[0064] Using the Phen / GCE modified electrode as the working electrode, the platinum electrode as the auxiliary electrode, and the Ag / AgCl as the reference electrode, the standard curve was drawn using the same method as in Comparative Example 1, and the corresponding linear regression equation was obtained.

[0065] (3) Sample testing

[0066] The detection method adopts the same sample detection method as that of Comparative Example 1, and the results are listed in Table 1.

[0067] Table 1 Test results of iron ion content in lithium hexafluorophosphate samples to be tested (n=3)

[0068]

[0069]

[0070] Note: 1#, 2# and 3# are lithium hexafluorophosphate samples from different batches, and the iron ion content test results are the average values ​​of 3 parallel tests.

[0071] As can be seen from Table 1, the Phen / PTCA / NH2-MIL-125 / GCE modified electrode used in the electrochemiluminescence method of the present invention has high sensitivity for the detection of trace iron ions, and the minimum detection limit is 3.5×10 -15mol / L, this is because the PTCA / NH2-MIL-125 composite material and o-phenanthroline (Phen) simultaneously modified the glassy carbon electrode, which not only improved the luminescence intensity and stability of the modified electrode, but also improved the selectivity for iron ions, so that the difference in luminescence intensity before and after the addition of iron ions showed a good linear relationship with the iron ion concentration, which was beneficial to the sensitivity of iron ion detection. However, the PTCA / NH2-MIL-125 alone modified glassy carbon electrode in Comparative Example 1 and the Phen alone modified glassy carbon electrode in Comparative Example 2 were low in sensitivity as ECL sensors, and trace iron ions in lithium hexafluorophosphate could not be detected.

[0072] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. An electrochemiluminescence method for detecting iron ions, characterized in that: The Phen / PTCA / NH2-MIL-125 / GCE modified electrode was used as the working electrode of the electrochemiluminescence test, the platinum electrode was used as the auxiliary electrode, and the Ag / AgCl was used as the reference electrode to form a three-electrode system, and the electrochemiluminescence method was used to detect iron ions. The preparation of the Phen / PTCA / NH2-MIL-125 / GCE modified electrode comprises the following steps: (1) Adding NH2-MIL-125 material and perylene tetracarboxylic acid into an ethanol solution, dispersing them uniformly, centrifuging and washing and drying them to obtain a light red powder, namely the PTCA / NH2-MIL-125 composite material; (2) dispersing the PTCA / NH2-MIL-125 composite material obtained in step (1) in DMF to obtain a DMF solution of the PTCA / NH2-MIL-125 composite material; (3) The DMF solution of the PTCA / NH2-MIL-125 composite material obtained in step (2) and the o-phenanthroline aqueous solution are mixed, and then drop-coated on the glassy carbon electrode, and then dried under an infrared lamp to obtain a Phen / PTCA / NH2-MIL-125 / GCE modified electrode.

2. An electrochemical luminescence method for detecting iron ions according to claim 1, characterized in that, The preparation method of the NH2-MIL-125 material is: Perylenetetracarboxylic acid and 2-aminoterephthalic acid are added to a mixed solution of DMF and methanol, mixed evenly to obtain a yellow milky liquid, which is then transferred to a high-pressure reactor for reaction. After the reaction is completed, the product is centrifuged, washed, and dried to obtain a yellow powder, namely the NH2-MIL-125 material.

3. An electrochemiluminescence method for detecting iron ions according to claim 1, characterized in that, The preparation method of perylene tetracarboxylic acid is as follows: perylene tetracarboxylic dianhydride is dissolved in NaOH, and then stirred to react to obtain a yellow-green solution, and then HCl is added dropwise until complete precipitation, and then fully washed with deionized water and dried to obtain a dark red powder, namely perylene tetracarboxylic acid.

4. An electrochemiluminescence method for detecting iron ions according to claim 1, characterized in that: The mass ratio of the NH2-MIL-125 material and perylene tetracarboxylic acid in step (1) is 3:1, and the total concentration of the solution obtained after the two substances are added with ethanol is 1 mg / mL; The mass concentration of the PTCA / NH2-MIL-125 composite material in the DMF solution of the PTCA / NH2-MIL-125 composite material in step (2) is 1 mg / mL; The concentration of the o-phenanthroline aqueous solution in step (3) is 5.0×10 -3 mol / L.

5. An electrochemiluminescence method for detecting iron ions according to claim 1, characterized in that: The specific steps include: (1) Prepare PBS buffer solution containing K2S2O8; (2) Drawing of standard curve: Adding iron ions to the PBS buffer solution containing K2S2O8 obtained in step (1) to obtain a series of iron ion standard solutions with different concentrations; The three-electrode system is immersed in the above-mentioned standard solutions of iron ions of different concentrations, and the PBS buffer solution containing K2S2O8 obtained in step (1) is used as a blank solution. In the electrochemical window range of -1.6 to 0 V, a photomultiplier tube high voltage of 800 V and a scan rate of 0.1 V / s are used to perform cyclic voltammetry scanning, and the potential-luminescence intensity curve is recorded. A linear relationship between the difference in luminescence intensity before and after the addition of iron ions and the logarithm of the iron ion concentration is established to obtain a corresponding linear regression equation, and the corresponding curve is the standard curve; (3) Sample testing The iron ion-containing sample to be tested is pretreated, and then the luminescence intensity is tested according to the method and test conditions described in step (2), and the iron ion concentration in the sample to be tested is calculated using the linear regression equation obtained in step (2).

6. The electrochemiluminescence method for detecting iron ions according to claim 5, characterized in that: The molar concentration of K2S2O8 in the PBS buffer solution containing K2S2O8 in step (1) is 0.05 mol / L, the molar concentration of PBS is 0.1 mol / L, and the pH of the PBS buffer solution containing K2S2O8 is 7.

5.

7. An electrochemiluminescence method for detecting iron ions according to claim 5, characterized in that: The concentration range of the iron ion standard solution in step (2) is 1.0×10 -14 mol / L~1.0×10 -7 mol / L, and the soaking time is 15 min.

8. The electrochemiluminescence method for detecting iron ions according to any one of claims 1 to 7, characterized in that: The method is used to detect iron ions in lithium hexafluorophosphate.

Citation Information

Patent Citations

  • Electrochemical luminescence method for detecting diethylstilbestrol

    CN110988067A

  • Electrochemical luminescence sensor based on resonance energy transfer and preparation method and application thereof

    CN111198221A